THE ROLE OF THE MODERN INFORMATION TECHNOLOGY IN PROFESIONAL COUNSELLOR'S WORK - PIETRUK, Witold (Trends in education, 2010)
The article shows the role of the modern information and communication technology which are the basic range of the knowledge that the counsellor should have. It is also shown that the easy access to educational and profesional information is the base of all counsellor's activity. The article stresses the importance of the Internet as a source of information thanks to which the decisions of the choice of school and the appropriate education profile can be made. The next aspect shown in this article concentrates on the using of the computer. Especially useful is the datebase, as well as a wide range of computer programmes that are helpful in four aspects of counselling process (self-estimation, getting information, adaptation of possibility, making decisions).
Keywords: Profesional counselling; The modern information technology; The computer in counsellor's work.